Novel Virkon S releasing alginate beads for water disinfection: synthesis, characterization and antimicrobial activity analysis - Mustafa, Faisal Suleiman; Sanliturk, Gizem; Guran, Mumtaz; Gazi, Mustafa (Springer, 2021)
Using of polymer encapsulated beads with antimicrobial agents is a novel and very promising strategy. In this study, a natural polymer; Sodium alginate, was used to encapsulate the very efficient disinfection agent; Virkon S for the first time. Preparation and characterization of beads was done by FTIR, UV/Vis and microscopy. Quantitative releasing of Virkon S from beads was also analyzed. After chemical analyses, microbiological analysis was done by performing time-kill assays to assess time-dependent antimicrobial activity of beads. These assays were performed by simulating contaminated water which contained three types of standard bacterial strains separately; Methicillin Sensitive Staphylococcus aureus (MSSA), Methicillin Resistant Staphylococcus aureus (MRSA) and Escherichia coli (E. coli). The results showed that more than 50% of Virkon S was released at 90th min and releasing was totally stabilized after 30 h. The time-killing assays indicated that the beads can effectively inhibit the growth of different bacteria including antibiotic resistant strains in water. 100.00 mg weighed beads killed all of the MRSA, MSSA and E. coli cells successfully at 15th, 120th and 180th min of contact time respectively. Our results showed that, Virkon S-alginate beads can be considered as promising disinfecting agents for several applications ranging from remediation of environmental water sources to cleaning of the various liquids in hospital setting.
Keywords: Virkon S; alginate beads; Controlled releasing; Disinfection agent